2015
DOI: 10.1136/jnnp-2014-309903
|View full text |Cite
|
Sign up to set email alerts
|

Establishing pathological cut-offs of brain atrophy rates in multiple sclerosis

Abstract: ObjectiveTo assess whether it is feasible to establish specific cut-off values able to discriminate ‘physiological’ or ‘pathological’ brain volume rates in patients with multiple sclerosis (MS).MethodsThe study was based on the analysis of longitudinal MRI data sets of patients with MS (n=206, 87% relapsing–remitting, 7% secondary progressive and 6% primary progressive) and healthy controls (HC; n=35). Brain atrophy rates were computed over a mean follow-up of 7.5 years (range 1–12) for patients with MS and 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
226
5
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 189 publications
(258 citation statements)
references
References 38 publications
22
226
5
5
Order By: Relevance
“…These values translate to a loss of 0.68%, 0.57%, and 0.45% per year, respectively. Only in the subgroup with no on‐study inflammatory activity and no confirmed progressions (28% of the placebo population) did the annualized rate of brain volume loss (0.38%) approach the proposed cutoff that separates pathologic from physiologic rates of brain volume loss (0.37% per year) 16. All the other disease course subgroups had higher rates of brain volume loss.…”
Section: Resultsmentioning
confidence: 99%
“…These values translate to a loss of 0.68%, 0.57%, and 0.45% per year, respectively. Only in the subgroup with no on‐study inflammatory activity and no confirmed progressions (28% of the placebo population) did the annualized rate of brain volume loss (0.38%) approach the proposed cutoff that separates pathologic from physiologic rates of brain volume loss (0.37% per year) 16. All the other disease course subgroups had higher rates of brain volume loss.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, brain volume declines more rapidly in MS patients when compared to age‐matched healthy controls (HCs) 3, 4, 5, 6. Across MS phenotypes, SPMS shows the fastest annual rate of brain atrophy, which is estimated to be 0.6% (compared to around 0.2% in age‐matched HCs) 5.…”
mentioning
confidence: 99%
“…Indeed, while WM volume shows a mild reduction during the course of disease, GM volume significantly and progressively decreases [5][6][7][8][9][10][11][12][13]. Recently, a parenchymal loss of ≥0.4% per year was proposed as "pathological atrophy rate" in MS patients [14].…”
Section: Introductionmentioning
confidence: 99%